Can the Reclassification of Other Comprehensive Income Narrow the Opportunities for Creative Accounting: Earnings Management and Income Smoothing? - Marhaendra Kusuma (Institute of Research and Community Outreach - Petra Christian University, 2023)
So far, research in Indonesia examines that the factors that influence creative accounting are the application of Good Corporate Governance, leverage, company size, and political connections, while research on the effect of other comprehensive income (OCI) as a result of the application of fair value accounting has not been widely carried out. This study finds evidence that aggregate OCI accumulation does not affect earnings management and income smoothing. However, testing on group OCI items that will be reclassified to net income has a negative effect. Asset realization commitment increases the negative effect of OCI on earnings management and income smoothing. Creative accounting through OCI can be done through a policy of delaying the realization time and or reducing the real amount of assets realized to get the net profit value according to the interests of management and the subjectivity of determining the fair value of assets and liabilities.